Trends and challenges of AAV-delivered gene editing therapeutics for CNS disorders: Implications for neurodegenerative disease - Boris Kantor; Bernadette O'Donovan; Ornit Chiba-Falek (Molecular Therapy: Nucleic Acids)
Recent advances in gene-editing technologies offer new opportunities for drug development to treat unmet medical needs in central nervous system (CNS) disorders including neurogenerative diseases of the aging brain. The adeno-associated virus (AAV) is a promising and most widely utilized vector for gene therapy application including the CNS. AAV is characterized by high transduction efficiency in both dividing and non-dividing cells, low immunogenicity and toxicity, and exceptional tissue specificity. The development of clustered regularly interspaced short-palindromic repeat (CRISPR)-based technologies has revolutionized all aspects of modern sciences and created an innovative therapeutic toolkit with the potential to address a wide range of neurological diseases, including Alzheimer’s (AD) and Parkinson’s (PD) diseases. However, AAV limitations for delivering CRISPR modalities continue to impede viable therapeutic interventions targeting the brain. This review highlights challenges and strategies to deliver AAV-CRISPR-based therapeutic cargos for gene therapy applications in the CNS, with a particular focus on AD and PD preclinical studies.